Continuous process for the epoxidation of terpenes using mesoscale oscillatory baffled reactors - Gunam Resul, Mohamad Faiz Mukhtar; Abdul Rehman; Fern´andez, Ana María L´opez; Eze, Valentine C.; Harvey, Adam P. (Elsevier, 2022)
Continuous epoxidation of terpenes with H2O2 was carried out using mesoscale oscillatory baffled reactors (meso-OBRs) in a solvent-free environment. The performance of the new 3D-printed single, tri- and multi-orifice baffles was compared with helical and integral baffles. The performance investigated includes mixing intensity, induction period, steady-state attainment, and heat removal capability of the meso-OBR. Moreover, passive isothermalisation was also investigated using meso-OBR in a heat pipe assembly. The tri- and multi-orifice baffles were able to overcome mixing limitations and achieved a comparable rate of reaction to batch at mixing conditions of Reo > 850 and Reo > 500, respectively. Both baffles exhibited rapid steady-state attainment, shorter induction period (t = 1.5τ) and better reproducibility with product variation of ∼1.3%. The meso-OBR designs demonstrated effective heat transfer capability, allowing the reaction to being operated isothermally with ±1 °C temperature variation in solvent-free conditions. This removes the need for a solvent, thus reducing reaction volume by a 5-fold. The timescale for the reaction was reduced from ∼8 h in a conventional process to 30 min in the multi-orifice meso-OBR, a 16-fold reduction. A better process has been developed for a continuous epoxidation of terpenes with H2O2 using multi-orifice meso-OBRs, with a potential intensification factor of ∼80.